Reverse shoulder arthroplasty for malunions of the proximal part of the humerus (type-4 fracture sequelae) - Raiss, Patric; Bruckner, Thomas; Zeifang, Felix; Loew, Markus (The journal of bone & joint surgery. A, American volume, 2016)
Background: - The treatment of fracture sequelae of the proximal part of the humerus in combination with posttraumatic arthritis is challenging. The reported results of treatment with anatomic shoulder arthroplasty are disappointing. The aim of this multicenter study was to analyze the clinical and radiographic results of reverse shoulder arthroplasty for treatment of posttraumatic sequelae of the proximal part of the humerus with malunion of the tuberosities. - Methods: - This was a retrospective, multicenter study of 42 patients (42 shoulders) with the diagnosis of posttraumatic sequelae of the proximal part of the humerus with malunions of the tuberosities who were treated with reverse shoulder arthroplasty between 2000 and 2010. The mean age at the time of arthroplasty was 68 years (range, 27 to 83 years; median, 70 years). The dominant side was treated in 24 cases. The mean clinical and radiographic follow-up was 4 years (range, 2 to 13 years; median, 3.5 years). The Constant score including subgroups, shoulder flexion, rotation motion, and radiographs of the affected shoulders were analyzed before the surgical procedure and at the time of the latest follow-up. Patients categorized their postoperative results as very good, good, satisfactory, or unsatisfactory. - Results: - The mean Constant score increased from 19.7 points (range, 0 to 52 points) preoperatively to 54.9 points (range, 21 to 83 points) postoperatively (p < 0.0001). All of the subgroups of the Constant score also increased, as did active shoulder flexion and external rotation (all p < 0.0001). In one case, loosening of the humeral and glenoid components occurred. Scapular notching was present in 22 shoulders (52%) and was grade 1 in 12 cases, grade 2 in 4 cases, grade 3 in 2 cases, and grade 4 in 4 cases. Complications occurred in 4 patients (9.5%). Eighteen patients (43%) rated their result as very good, 19 (45%) rated their result as good, 4 (10%) rated their result as satisfactory, and one (2%) rated the result as unsatisfactory. - Conclusions: - Reverse shoulder arthroplasty is a viable treatment option for type-4 proximal humeral fracture sequelae that cannot otherwise be treated with anatomic shoulder replacement. - Level of Evidence: - Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.
Gesehen am 17.02.2021